Penerapan Undang- Undang Nomor 23 Tahun 2011 Terhadap Legalitas Pengelolaan Zakat - Erni susilawati (AGHNIYA : Jurnal Ekonomi Islam, 2019)
Zakat as a pillar of Islam is a definite obligation (qath'i), which is established by Allah SWT to Muslims who can afford it and is intended for those who are less fortunate. The amil zakat institution in Indonesia has binding provisions in receiving, managing and distributing zakat funds to the poor. In the Law Number 23 Year 2011, it is affirmed the obligation of LAZ to report the collection and utilization of zakat activities that have been done to BAZNAS, and not the obligation to deposit zakat to BAZNAS. Looking at some of the contents of the latest Law Number 23 of 2011, there are several important points that we must have further. One of them is the issue of zakat management which is now focused on the Government or the centralization of zakat on BAZNAS.The purpose of this study is to look at the Application of the Zakat Management Act Number 23 of 2011 to the Legality of the Management of Zakat by the National Amil Zakat Agency of North Sumatra Province. The method used in conducting this research is qualitative descriptive. The method that analyzes and describes the Legality of the Management of Zakat on Zakat Management and the Application of Law Number 23 of 2011 by the North Sumatra National Zakat Amil Agency.The results of the study can be concluded that the management of zakat is an activity of planning, implementing and coordinating the collection, distribution, utilization and reporting of zakat. The management of zakat is carried out based on the number of principles, namely Islamic Law, Trust, Justice, Legal Certainty, Integrated and Accountability. BAZNAS as a definitively regulated institution in the Law also has an independent nature. The independent nature is regulated in article 5 paragraph 3 of the zakat management law, there are two other elements regulated in the article, namely BAZNAS as a Non Structural Government institution, and BAZNAS which is responsible to the President through the Minister of Agriculture.Keywords: Zakat, Zakat Management, Law No. 23 of 2011 concerning Management of Zakat